1964
DOI: 10.1037/h0047591
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a high-school program for potential dropouts.

Abstract: Approximately 75 potential dropouts (29 classified as "aggressive", 46 as "passive") were exposed to a program that differed from the regular school program in 4 main ways: (a) a small, stable pupil-teacher ratio; (b) a vocational curriculum; (c) a counselor immediately available; and (d) afternoon jobs for pay and school credit. Evaluation was in terms of drop-out rates, police contact rates, and attitudes assessed by before-after interviews; comparison was with an equal number of potential dropouts enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1965
1965
1969
1969

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Treatment of the potential dropout is not easy (cf. Longstreth, Shanley, & Rice, 1964), but it is more likely to succeed if it is addressed to the underlying factors brought into view by proper diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the potential dropout is not easy (cf. Longstreth, Shanley, & Rice, 1964), but it is more likely to succeed if it is addressed to the underlying factors brought into view by proper diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Longstreth, Shanley, and Rice (1964) is in one sense typical of many programs (small pupil-teacher ratio, vocational curriculum, counseling, and work experience), but in another sense it is quite distinctive in its inclusion of a control group. Studying high school students who were potential dropouts and subdividing them into an "aggressive" and a "passive" group, they found that a three-year program produced no difference between groups in incidence of dropout or in police contact.…”
Section: Educational Programsmentioning
confidence: 99%
“…The most technically sophisticated study was done by Longstreth, Stanley & Rice (1964). Using a variety of measures, they concluded that the program had only innocuous educational and vocational effects, despite the fact that the students were very supportive of it.…”
mentioning
confidence: 97%